A pseudo-3D ball lattice artifact and method for evaluating the metrological performance of structured-light 3D scanners. (October 2019) - Ghandali, Pooya; Khameneifar, Farbod; Mayer, J.R.R.
Highlights: A pseudo-3D artifact for performance evaluation of structured-light scanners. Testing the scanner accuracy in its entire measurement volume. The procedure does not require the alignment of reference data with the scan data. The uncertainty of reference data is estimated. Abstract: This paper presents a novel reference artifact and procedure for assessing the metrological performance of structured-light 3D scanners, also known as fringe projection systems. Despite the increasing popularity of these scanners, there is still no international standard aiming at providing a guideline for how to evaluate their metrological performance. The users of the scanners, especially for part inspection, need instructions for comparing the accuracy of different systems in measuring specific parameters, as well as acceptance tests to verify whether a particular scanner can be used to inspect the part in question. As the structured-light scanners are area-scanning systems, they necessitate testing over their entire measurement volume. In order to enable this, we propose a method based on a pseudo-3D artifact calibrated by a contact probe on a coordinate measuring machine (CMM). The proposed artifact consists of a 2D ball plate that is mounted on top of spacers of different heights using kinematic couplings that ensure repeatable positioning of the ball plate with respect to the base in order to create a 3D lattice once measured. The artifact provides reference values for the distance between the centers of any pair of precision balls, as well as the reference for size and form, in order to benchmark the scanner measurements. Using the reference data, the proposed procedure enables acceptance tests and a comprehensive insight into the errors of the scanner in measuring distance, size, and form at different positions within its entire scanning volume.